2016
DOI: 10.4103/ipj.ipj_98_14
|View full text |Cite
|
Sign up to set email alerts
|

Coping, perceived stress, and job satisfaction among medical interns: The mediating effect of mindfulness

Abstract: Background:Past research studies on the exploration of attributes to the stress of doctors/medical interns were reported more often than the types of coping strategies, healthy practices to strengthen their internal resources to deal effectively with the stressful situations.Objectives:The present study was conducted to find such internal resource – “mindfulness” as a mediator of coping, perceived stress, and job satisfaction among medical interns.Methods:A cross-sectional descriptive study comprised 120 medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 33 publications
2
24
0
1
Order By: Relevance
“…As in other studies, we found direct relationships between burnout and stress, 36 , 37 self-compassion and mindfulness, 38 , 39 and self-compassion and resilience. 40 , 41 We found inverse relationships between stress and mindfulness, 42 , 43 burnout and self-compassion 40 , 44 and the emotional exhaustion component of burnout and resilience, 45 , 46 also reported previously. We found a weaker correlation of empathy components (only depersonalization component of burnout was significantly correlated with perspective taking component of empathy), showing a weaker relationship between burnout and empathy overall.…”
Section: Discussionsupporting
confidence: 86%
“…As in other studies, we found direct relationships between burnout and stress, 36 , 37 self-compassion and mindfulness, 38 , 39 and self-compassion and resilience. 40 , 41 We found inverse relationships between stress and mindfulness, 42 , 43 burnout and self-compassion 40 , 44 and the emotional exhaustion component of burnout and resilience, 45 , 46 also reported previously. We found a weaker correlation of empathy components (only depersonalization component of burnout was significantly correlated with perspective taking component of empathy), showing a weaker relationship between burnout and empathy overall.…”
Section: Discussionsupporting
confidence: 86%
“…Strengthening their coping resources at work and guiding them to adopt emotion-and problemfocused strategies are critical to assist them to cope with daily stressors. 57 Because of the cultural diversity of women healthcare professionals in the UAE healthcare system, there is a need to individualise stress management coping techniques to target and consider all potential mediators of stress across different groups of women. 57 Although 60% of participants reported poor subjective sleep quality, morning and bedtime salivary cortisol levels were not significantly correlated with quality of sleep.…”
Section: Discussionmentioning
confidence: 99%
“…57 Because of the cultural diversity of women healthcare professionals in the UAE healthcare system, there is a need to individualise stress management coping techniques to target and consider all potential mediators of stress across different groups of women. 57 Although 60% of participants reported poor subjective sleep quality, morning and bedtime salivary cortisol levels were not significantly correlated with quality of sleep. A previous study investigated the effects of sleep quality and quantity on cortisol response to acute stress among 73 younger adults.…”
Section: Discussionmentioning
confidence: 99%
“…Stress is defined as any discomfort perceived by the individual that is stimulated by activities perceived as too intense and frequent, which exceed a person’s coping capabilities and resources to manage. Successfully management or minimization of stress depends on the individual’s ability to identify and adapt using coping strategies 1. The purpose of coping is to maintain psychological health and inhibit manifestations of stress-associated symptoms.…”
mentioning
confidence: 99%